Pengembangan Bahan Ajar Berbasis NHT Pada Mata Pelajaran IPA Materi Macam-Macam Gaya Untuk Siswa Kelas IV SD - Sukrandi Okta; Endang Widi Winarni; Abdul Muktadir (UNIB Press, 2023)
This research aims to develop NHT-based teaching materials for science subjects in various styles for fourth grade elementary school students. The type of research in this research is research and development or Research and Development (R&D) ADDIE model. The results of this research show 1. The first stage was carried out by analyzing the needs analysis curriculum in Class IV of SD Negeri 119 Kaur. The design stage was carried out by preparing a product plan for NHT-based science teaching materials on materials of various styles for grade IV elementary schools based on the results of curriculum analysis, analysis of teacher and student needs. The product design carried out in developing NHT-based teaching materials is as follows: (a) compiling teaching materials, (b) format selection, (c) initial design. 2. Material suitability has an average Aiken's V number of 0.80 (Very Valid), language suitability has an average Aiken's V number of 0.98 (Very Valid), presentation feasibility, namely validation results, has an average Aiken's V number of 0.85 ( Very Valid). Based on the validation results from the third aspect, it can be concluded that the product is suitable for use. 3. NHT-based teaching materials in various class IV styles are considered effective in improving student learning outcomes in science learning.